Visualization of Accounting and Indigenous People Research: A Bibliometric Review Using R - Thahirah, Khadijah Ath; Triyuwono, Iwan; Mulawarman, Aji Dedi; Achsin, M. (Society of Visual Informatics, 2025)
This study aims to map out the evolution of research trends on accounting and Indigenous peoples by using bibliometric analysis. Most bibliometric literature articles rely on basic graphical representations generated by computer systems. The methodology for conducting bibliometric analysis presented in this paper consists of three stages, namely data collection, software selection and analysis. This study used published papers from the Scopus database was carried out on 13 June 2024 and found 42 indexed research publications on the topic of accounting and indigenous people between 1999 and 2023. The map of research development in the field of accounting and Indigenous people is obtained through the export process, which was analyzed using the R Biblioshiny application program. The findings demonstrated a development trend with a static increase in the number of publications about accounting and research on Indigenous people. Besides, the results show that the journal with the most publication and impact is the Accounting, Auditing, and Accountability Journal. The country with the most objects of study is Australia. The development of research related to accounting and Indigenous People was growing, although not too massive. Along with these conditions, various trends in Accounting and Indigenous People Research topics grew. The results of this study also indicate that the most widely used topic keywords are Accounting, Indigenous, People, and Research. The findings of this study provide scholars with a comprehensive understanding of the current research work in the field of accounting and indigenous people and its future directions.